FAUNA MOLUSKA DI PERAIRAN TEPI DANAU SINGKARAK SUMATERA BARAT KOMPOSISI DAN KEPADATAN JENISNYA - MARWOTO, RISTIYANTI M.; DJAJASASMITA, MACHFUDZ (BERITA BIOLOGI, 1986)
RISTIYANTI. M. MARWOTO & M. DJAJASASMITA. 1986. Competition and population density of the molhiscan fauna in Lake Singkarak, West Sumatera. Berita Biologi 3(6): 293 - 296.A study of the competition and density of the molluscan fauna of coastal water in Lake Singkarak, West Sumatera, has been carried out in October 1982. The molluscs collection consisted of 4 thiarids (Brotia costula, Melanoides granifera, M. tuberculata and Thiara scabra), 2 planorbids (Gyraulus feunerborni and G. sumatranusj, 1 bulimid (Emmericiopsis lacustris) and 1 corbiculid clam (Corbicula moltkeana).The stony and sandy coastal 2 water is dominated by B. costula (59/0.09 m ) 2followed by C. molticeana'(32/0.09 m ), E. lacus- 2 2 tris (31/0.09 m ), M. tuberculata (21/0.09 m ) 2 and the other species 1 - 10/0.09 m .The water quality (temperature 27.7°C, pH 6.3, alkalinity 88.5 ppm and disolved oksigen 7.95) and food (detritus and periphyton) seems to be adequate to wpport the molluscan life.